A proposed educational media center for the Division of City Schools, Manila - Plana, Modesta R.
This study surveyed the existing conditions pertinent to the educational media program of the public schools in the Division of City Schools, Manila, with the end in view of providing empirical support to a proposed Educational Media Center for the Division. Normative survey was largely used to gather enough data that will give a true and objective picture of the Educational Media Program.